RESULTS AND PROSPECTS OF PEA BREEDING - I. P. Kotlyar; E. P. Pronina; V. A. Ushakov (Овощи России, 2016)
In the laboratory of leguminous crops of the “All-Russian Scientific Research Institute of vegetable breeding and seed production”, more than 100 samples of pea are studied annually. As a result, pre-breeding collection of the sources of agronomical valuable traits was developed. It is utilized for development of new pea varieties resistant to lodging. In 2012- 2014, the crossing were conducted. As a result of selection in F2-F6, the lines of different groups of maturity with lodging resistance were selected. These transgressing forms are suitable for canning, deep freezing, and drying. The following samples are recommended for development of high yielded varieties: «102- 82А5Б4» is the middle-early variety, the progenitor of early ripening cv. «Korsar» applied for the state variety trial in 2015 and two promising samples «15 КСИ 15» and «9 КСИ». The «16-05» is the middle-early variety, the transgressive form for the trait «seed amount per nod» with high attachment of lower bean. The sample «K-8915» is the middle-early genotype, high productive, with high attachment of lower bean. The sample «Troyika» is recommended for development of high productive, late ripening initial breeding material. As a result of step crossing this sample is characterized by late maturity, by three bean per nod, and by high attaching of lower bean. The sample «CM-10 m» is distinct in the aphyllous type of leaf, resistance to powdery mildew, paired bean, suitable for canning and drying. This sample was selected as a transgressive form for stem anatomy structure (spongy cell tissue) from sample developed by complex step hybridization. Owing the distinctive feature in the stem anatomy structure, this sample can be recommended as a main parental form for development of varieties resistant to lodging.